CFD Analysis to explain the Operating range extension observed during Operation in Co-rotating Mode of a Twin-impeller Centrifugal Compressor - Nguyen Van-Thang (EDP Sciences, 2021)
Centrifugal compressors are widely used in many industrial applications because of their advantages. However, these turbomachines suffer at a low-flow rate from instabilities, such as rotating stall and surge. That leads to operational failure, pressure fluctuations and vibrations of the thorough system. Many mechanical solutions minimize these instabilities and expand the operating range towards low-flow rates like active control of the flow path, variable inlet guide vane and casing treatment. Currently, our team has developed a new compressor composed of a twin-impeller powered by autonomous systems. We notice the performance improvement and instabilities suppression of this compressor experimentally. In this paper, a CFD study is presented to explain some of these experimental observations by analyzing the inside of twin-impeller, the flow structures and thermodynamic characteristics at low flow rates operating in a co-rotating mode. Numerical results and experimental measurements of compressor maps are consistent.